2015
DOI: 10.1103/physreva.91.043413
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of resonant Auger processes using a strong bichromatic field

Abstract: We theoretically investigate the effects of strong couplings in resonant Auger processes under the combination of strong resonant x-ray and nearly resonant optical pulses. The x-ray field couples the ground state with a core-excited state, while the optical field couples the core-excited state with another core-excited state of opposite parity. The Auger electron spectrum changes its shape as the intensities of the x-ray and/or optical fields increase, and at sufficiently high intensities we observe that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…is complex from the aspect of Autler-Townes splitting, it manifests clearly an asymmetric lineshape with the changes of t, similar to the Fano profile resulting from the interference of the transition to the bound state embedded in the continuum [32,34,[52][53][54]. As was recently approved, the laser control allows us to manipulate the interference and as the results of changing the lineshape of the transient absorption spectra from the Lorentz to Fano profile [31,55,56].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…is complex from the aspect of Autler-Townes splitting, it manifests clearly an asymmetric lineshape with the changes of t, similar to the Fano profile resulting from the interference of the transition to the bound state embedded in the continuum [32,34,[52][53][54]. As was recently approved, the laser control allows us to manipulate the interference and as the results of changing the lineshape of the transient absorption spectra from the Lorentz to Fano profile [31,55,56].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Recent availability of free electron lasers (FEL) has created access to high intensity ultrashort x-ray pulses that can set off inner shell processes like that of the RA process, and is providing opportunities for re-investigating the RA process under high intensity x-ray lasers. Such an exercise has already offered us insights into many interesting phenomena associated with the RA process [11][12][13][14][15][16][17][18]. One such phenomenon is the line splitting in the electron spectrum of the Auger electrons, released from the core-excited state into the associated continuum, because of x-ray induced Rabi oscillations between the ground and core-excited state [15].…”
Section: Introductionmentioning
confidence: 99%
“…That control causes a fingerprint in the Auger spectrum. Previous studies have demonstrated how such short pulses may affect resonant Auger spectra with a single high-intensity x-ray pulse [14][15][16][17][18][19], a single x-ray pulse with an optical field, [20][21][22][23][24] and two-color x-ray pulses. [25,26] The normal (nonresonant) Auger process is usually described by a two step model in which core-hole ionization and Auger decay are treated independently.…”
Section: Introductionmentioning
confidence: 99%